Pengaruh Kewajaran Harga, Kualitas Layanan, dan Nilai Yang Dirasakan terhadap Kepuasan Pelanggan serta Dampaknya Terhadap Kepercayaan: Studi pada Pengguna Maxim di Semarang - Devi Lestari; I Made Sukresna (Diponegoro Journal of Management, 2025)
The advancement of digital technology has brought significant transformation across various sectors, including transportation services. One of the manifestations is the emergence of online transportation platforms such as Maxim, which offers relatively lower prices compared to its competitors. However, negative perceptions regarding service quality and price transparency, especially in Semarang, have raised concerns. This prompts an investigation into the extent to which factors such as price fairness, service quality, and perceived value influence customer satisfaction and, in turn, affect users’ trust in the service. This study employs a quantitative approach using non-probability sampling with a purposive technique. The sample consists of 102 active Maxim users in Semarang. Data were collected through an online questionnaire via Google Form and analyzed using SmartPLS 4.0 software. The variables examined include price fairness, service quality, perceived value, customer satisfaction as a mediating variable, and customer trust as the dependent variable. Measurement and structural model analyses were conducted to assess the validity, reliability, and relationships between variables.The findings indicate that price fairness, service quality, and perceived value have a positive and significant effect on customer satisfaction. Furthermore, customer satisfaction has a positive and significant effect on customer trust toward Maxim's service. These results imply that companies must emphasize fair pricing, improve service quality, and create added value for customers to foster greater trust and loyalty in the context of online transportation services.